2015
DOI: 10.1038/nrrheum.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Optimized treatment algorithms for digital vasculopathy in SSc

Abstract: Early identification of secondary Raynaud phenomenon is essential to treat the underlying disease—most frequently systemic sclerosis (SSc). Integrated therapeutic approaches and monitoring systems that offer improved modalities of care feature in the new best practice recommendations for the treatment of digital vasculopathy in SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…This evidence allowed us to hypothesize that the above-mentioned profibrotic switch may be considered a normal response of MVECs in any physiological (wound healing) [ 33 ] and pathological (SSc) [ 34 ] conditions characterized by overexpression of ET-1 and TGF-β. In this setting, considering the synergistic action of ET-1 and TGF-β in triggering EndoMT [ 35 ], our study strengthens the fundamental therapeutic utility that blocking the ET-1 system, by using dual endothelin-1 receptor antagonists (ERA), could represent an important therapeutic strategy [ 36 ]. Our in vitro model demonstrates that both BOS and MAC are effective in inhibiting the ET-1/TGF-β-mediated EndoMT, supporting the hypothesis that ET-1 may represent the ultimate mediator of TGF-β actions [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 53%
“…This evidence allowed us to hypothesize that the above-mentioned profibrotic switch may be considered a normal response of MVECs in any physiological (wound healing) [ 33 ] and pathological (SSc) [ 34 ] conditions characterized by overexpression of ET-1 and TGF-β. In this setting, considering the synergistic action of ET-1 and TGF-β in triggering EndoMT [ 35 ], our study strengthens the fundamental therapeutic utility that blocking the ET-1 system, by using dual endothelin-1 receptor antagonists (ERA), could represent an important therapeutic strategy [ 36 ]. Our in vitro model demonstrates that both BOS and MAC are effective in inhibiting the ET-1/TGF-β-mediated EndoMT, supporting the hypothesis that ET-1 may represent the ultimate mediator of TGF-β actions [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 53%
“…Macrophage-released MMP-9 contributes to fibrosis by inducing the activation of myofibroblasts, playing an important role in the pathogenesis of diseases characterized by an inflammatory etiology and extracellular matrix remodelling that requires selected therapies [44,4751]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other authors observed no effect on microvascular structure and function when ERA treatment was administered to patients with SSc for short-term therapy and in monotherapy, probably because of a too-short interval between sequential NVC observations 36,37,38 .…”
Section: Discussionmentioning
confidence: 94%